TRAUMAS IN PREGNANT WOMEN: THE MODERN ASPECTS OF THE PROBLEM (THE REVIEW OF THE LITERATURE) - Z. D. Karimov; U. U. Jabborov; B. S. Abdikulov; M. T. Husanhodzhaeva (Неотложная медицинская помощь)
Abstract. In the format of the information and analytical review of the literature provides the data on injuries among pregnant women. The influence of different mechanism, the degree of the severity and nature of injuries on maternal and perinatal outcomes were shown in the article. The revealed-mined some contradictions had been detected in the results of studies on trauma outcomes depending on the severity and nature, as well as the lack of information on standards of conduct and protocols.